2023
DOI: 10.2147/ndt.s415937
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Mobile Phone App for Depressed Mood in Young Adults with Subthreshold Depression: A Pilot Randomized Controlled Trial

Hitomi Ejiri,
Hiroyuki Uchida,
Kenji Tsuchiya
et al.

Abstract: Background: Preventive interventions for subthreshold depression (StD) are essential to reduce the incidence of major depressive disorder. Our smartphone application presenting positive word stimulation in video (ie, Subliminal Priming with Supraliminal Reward Stimulation, SPSRS) was suggested to improve depressive symptoms in people with StD, although it is unclear whether it can immediately improve depressed mood. This pilot randomized controlled trial (RCT) aimed to investigate the preliminary efficacy of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…This study used BDI-II to identify the presence of StD in older patients with cardiac disease and to measure changes in depressive symptoms during a 1-week intervention. This is because BDI-II, in addition to being widely used to identify StD, is also widely used to assess depressive symptoms in clinical populations, including patients with cardiac disease [ 65 , 70 , 86 89 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used BDI-II to identify the presence of StD in older patients with cardiac disease and to measure changes in depressive symptoms during a 1-week intervention. This is because BDI-II, in addition to being widely used to identify StD, is also widely used to assess depressive symptoms in clinical populations, including patients with cardiac disease [ 65 , 70 , 86 89 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, SPSRS is free of charge and uses the YouTube Application Programming Interface, which allows patients to select from a wide variety of videos of interest and work toward reducing depressive symptoms. Previous studies have suggested that the use of SPSRS among individuals with StD compared with no intervention not only improves their depressive symptoms [ 64 ], but may also improve depressed mood immediately after the 10-min intervention [ 65 ]. In addition to the existing studies showing the effectiveness of SPSRS interventions in reducing depressive symptoms in patients with StD, one of the major factors that renders SPSRS applicable to older patients with cardiac disease is that it allows them to work toward reducing depressive symptoms without moving from their bed.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, some studies have identified positive effects associated with short video usage. For example, a 10-minute short video featuring positive stimuli could potentially enhance health outcomes [26,41,42]. Additionally, smartphone-based medical monitoring has also been utilized for disease management [27].…”
Section: Relationship Between Short Video Use and Insomnia Symptomsmentioning
confidence: 99%